Pengaruh Waktu Operasional Alat Tangkap Pukat Cincin (Purse Seine) terhadap Hasil Tangkapan Ikan Teri Jengki (Stolephorus indicus) di Perairan Palang Tuban - Faisal Ali; Achmad Kusyairi; Alif Astagia (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Fishing in the waters of Palang Tuban are continuously carried out, one of which is the capture of jengki anchovies (Stolephorus indicus). The purse seine fishing gear is a productive and efficient tool for capturing jengki anchovies without requiring a fish aggregation device (FAD). Fishermen in Palang Waters often experience varying results, where some catch a large amount of fish, while others catch much less. Some fishermen operate their gear for shorter or longer periods, but this does not guarantee a higher catch. This study aims to determine the operational time of the purse seine gear on the catch of jengki anchovies, and also to examine the effect of different operational times on the catch. Data was collected through experiments with two different treatments, each repeated 16 times, totaling 32 data points. The main parameter analyzed in this study was the quantity or weight of the catch. The research method used was experimental fishing with t-test analysis. The results of the t-test with 16 repetitions at 04:00-10:00 WIB and 07:00-13:00 WIB showed average catches of 1.391 kg and 1.234 kg, respectively, with a significance (2-tailed) value of 0.340 > 0.05. The t-test results indicate that H0 is accepted, and H1 is rejected, meaning there is no significant difference between the two time periods.